Upaya Kontribusi melalui Keterlibatan Pengabdian Mahasiswa dalam Proses Konstruksi Pondasi Bored Piled Jembatan Timbang: Contribution of Student Community Service Involvement in the Bored Piled Weigh Bridge Foundation Construction Process - Zulfikar, Ryan; Noor, Rusandi; Firdaus, Muhammad Irkham (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This activity is a community service carried out by UMKT Civil Engineering students who are integrated with UMKT Civil Engineering Lecturers for two months. The collaboration carried out by students with industry partners in the weighing-bridge construction project showed an essential contribution to the integration of actual and theory. The focus of this community service activity is the implementation of work methods on bored pile foundation work. Student activities include direct observation, interviews, and comparative theory analysis with field practice. The activity results focus on Standard Penetration Test (SPT) soil testing data, determining weighing-bridge bored pile points, and implementation methods. Through this activity, students and lecturers play an active role in providing accurate contributions to industrial partners in ensuring the efficiency and quality of the implementation of bored pile foundations. Thus, this activity not only provides solutions to problems faced by industrial partners but also serves as a direct learning medium for students. This emphasizes the importance of an interdisciplinary approach that combines science, technology, practical expertise, and academic theory in planning bored pile foundations for weighbridges.